2021
DOI: 10.1111/1467-8551.12497
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Responses to the Coronavirus Crisis and their Impact on Electronic‐Word‐of‐Mouth and Trust Recovery: Evidence from Social Media

Abstract: This study examines how corporate responses to service failure, caused by the coronavirus (COVID-19) crisis, influence electronic-word-of-mouth (E-WoM) and trust recovery around lockdown, using multiple data sources. A dataset of 398 valid COVID-19 announcements from 50 UK food retailers posted on the social media platform Twitter, and 21,960 consumer comments associated with these announcements, are analysed using content analysis and social media analytics, respectively. In Study 1, we test the effects of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 78 publications
0
39
0
Order By: Relevance
“…As a result, we provide novel findings, compared to the findings of prior research (e.g., Novelli et al, 2018 ), suggesting that when formulating tourism crisis response, tourism practitioners should consider a shift in emphasis away from a response strategy per se towards focusing on linguistic cues and response framing. This is evident by a recent study undertaken by Wang et al (2021) where it was found that consumer trustworthiness could significantly recover when firms frame their COVID-19 related tweets in an emotional way, regardless of what response strategy is used.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As a result, we provide novel findings, compared to the findings of prior research (e.g., Novelli et al, 2018 ), suggesting that when formulating tourism crisis response, tourism practitioners should consider a shift in emphasis away from a response strategy per se towards focusing on linguistic cues and response framing. This is evident by a recent study undertaken by Wang et al (2021) where it was found that consumer trustworthiness could significantly recover when firms frame their COVID-19 related tweets in an emotional way, regardless of what response strategy is used.…”
Section: Discussionmentioning
confidence: 93%
“…Signalling theory provides the grounds to explain the various types of existing signals and the situations in which they are used ( Filieri, Raguseo, & Vitari, 2021 ; Spence, 2002 ). This theory has been frequently used to study relationship recovery ( Kharouf et al, 2020 ) organisational communication to customers ( Wang et al, 2021 ), and to assess product quality signals in eWOM research ( Filieri, Raguseo, & Vitari, 2021 ). In our study, signalling theory is applied to explain how tourism organisations (as signallers) utilize COVID-19 responses (as signals) posted on social media during the global pandemic crisis (as a signalling environment) to communicate with a wide range of consumers (as receivers).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Wang et al . ( 2021 ) stress the importance of action in response to the COVID‐19 crisis, examining the relationship between firm communication (signals), consumer response and impact on trust recovery. In a conceptual paper, Hitt et al .…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%